The association of lipid accumulation product with inflammatory parameters and mortality: evidence from a large population-based study - Yi Chi; Yiqing Zhang; Huang Lin; Shanshan Zhou; Genlin Jia; Wei Wen (Frontiers in Epidemiology)
BackgroundObesity is closely associated with lipid metabolism, and the accumulation of lipids leads to low-level inflammation in the body, which can trigger cardiovascular disease. This study aimed to explore the association between a novel marker of lipid accumulation, the abdominal volume index (AVI), inflammatory parameters, and mortality.MethodsThis study enrolled 2,109 older adult senior citizens (aged over 60 years) with hypertension from the National Health and Nutrition Examination Survey. The primary endpoints included all-cause mortality and cardiovascular mortality, which were assessed by linking the data to the National Death Index records. Cox regression model and subgroup analysis were constructed to investigate the associations between AVI and both all-cause and cardiovascular mortality. Restricted cubic splines were employed to further explore the relationships among AVI, inflammatory parameters, and mortality. By considering inflammatory factors as mediators, we investigate the mediating effects of AVI on mortality.ResultsAfter a median follow-up of 69 months, there were 1,260 deaths, with 337 attributed to cardiovascular causes within the older adult population studied. In the multivariable-adjusted model, AVI was positively associated with both all-cause and cardiovascular mortality [Hazard Ratio (HR) = 1.09, 95% CI = 1.06–1.11 for all-cause mortality; HR = 1.07, 95% CI = 1.03–1.12 for cardiovascular mortality]. Kaplan-Meier survival plots indicated an overall median survival time of 144 months. Mediation analysis revealed that Systemic Inflammatory Response Index (SIRI), Monocyte-to-HDL ratio (MHR), and Neutrophil-to-Lymphocyte ratio (NLR) mediated 27.15%, 35.15%, and 16.55%, respectively, of the association between AVI and all-cause mortality.ConclusionAVI is positively associated with all-cause mortality in older adults with hypertension, and this association appears to be partially mediated by inflammatory parameters.